INVOLVEMENT OF RESPONSIBLE EMPLOYEES IN THE FUNDAMENTAL REFORM OF THE FACTORS THAT LEAD TO CORRUPT SITUATIONS IN ORGANIZATIONS AND THEIR ELIMINATION (American Journal of Research in Humanities and Social Sciences, 2024)
Corruption within organizations has long been a widespread problem that undermines transparency, ethics, and overall organizational health. This research paper examines the factors that influence corruption and proposes a radical reform approach that emphasizes the participation of responsible officials in its elimination. By empowering and engaging employees, organizations can create a culture of honesty, accountability and ethical behavior, thereby reducing the risks associated with corruption. This article highlights key strategies and initiatives that can be implemented to eliminate corruption and create a sustainable, corruption-free organizational framework and enabling environment.